Two new species and one nomenclatural note in Myrtaceae from Santa Catarina, Brazil - Sobral, Marcos; Molz, Martin; Vieira, Fábio C.s. (Phytotaxa, 2019)
Here are described and illustrated Eugenia quiriri and Myrceugenia basicordata, from the southern Brazilian state of Santa Catarina, and Eugenia krapovickasiana is included in the synonymy of E. angelyana. Eugenia quiriri is morphologically related to Eugenia neotristis, but differs by its pilose twigs and blades and visibly pedicellate flowers. Myrceugenia basicordata is close to M. miersiana, but differs by its shorter petioles, oblong blades with sometimes cordiform base and ovaries with two locules. Additionally, conservation status is discussed for these species.